The Influence of Body Mass Index and Weight Loss on Outcome of Elderly Patients Undergoing Lung Cancer Resection - Fiorelli, Alfonso; Vicidomini, Giovanni; Mazzella, Antonio; Messina, Gaetana; Milione, Roberta; Di Crescenzo, Vincenzo Giuseppe; Santini, Mario (The Thoracic and Cardiovascular Surgeon, 2014)
Background The aim of the study was to evaluate the influence of nutritional status on outcome of elderly patients resected for lung cancer.Materials and Methods A total of 117 consecutive patients aged ≥ 70 years undergoing lung cancer resection were enrolled. In addition to routine preoperative evaluations, other variables such as body mass index, weight loss, serum albumin, lymphocytes, and transferrin were counted. According to the body mass index value, patients were divided into Group A (≤ 18.5, underweight) and Group B (> 18.5) and risk factors for morbidity and mortality were analyzed.Results Group A and Group B counted 21 and 96 patients, respectively. The mean age was 74.9 ± 2.6; body mass index of Group A was significantly lower than that of Group B (16.7 ± 1.3 vs. 23.5 ± 1.7, respectively, p < 0.0001). On multivariate analysis, significant risk factors for complications were pneumonectomy (p = 0.001), stage (p = 0.006), predictive postoperative flow expiratory volume in 1 second (ppoFEV1%) (p = 0.003), and coronary disease (p = 0.04) and significant risk factors for early mortality were pneumonectomy (p = 0.0002), ppoFEV1% (p < 0.0001), BMI (0.02), and weight loss (0.007). The median survival time of Group A and Group B was 41 versus 54 months, respectively (p = 0.1). However, body mass index of less than 18.5 (p = 0.01) and weight loss of > 5% before operation (p = 0.01) were independent risk factors for 1 year mortality.Conclusions In elderly patients, malnutrition was a significant additional risk factor for early death. Nutritional assessment should be included in the routine preoperative selection. In malnourished patients, nutritional support before and after operation and a careful postdischarge care might be beneficial, but it should be corroborated by further prospective studies.
Keywords: body mass index; weight loss; elderly patients; lung cancer; surgery